LAW ENFORCEMENT TO OFFENDERS’ RIGHTS BASED ON CONTEMPT OF COURT - Subarkah, Ibnu (Faculty of Law, Universitas Sebelas Maret, 2017)
In legal field, especially related to judicial field of judiciary, efforts to reform criminal law to and to overcome justice and certainty are done incessantly which means that law enforcement efforts need to be effected. Some situations and conditions may reduce judicial image if the law enforcement is lacking or not being noticed at all. The existence of cases through legal, research, academic thinking, as well as opinion of legal practitioners have varied the existence of judiciary images. Therefore, this research is specifically aimed to know, describe, and at the same time analyze the rights of defendants (offenders of rights) based on contempt of court.The method used in this study is qualitative research prioritizing quality and primary and secondary data types. The primary data are taken empirically from the field and the secondary data are taken from literature study, documentation, determination of respondents by purposive sampling in which the interviewee is a judge.The results show that, in practice, the rights of defendants are protected in accordance to the applicable provisions as well as the contempt of court issue. Due to the subjective perception of community in the course of trial, it is essentially needed to immediately draw up the Contempt of Court Law.Keywords: Law Enforcement, Offenders’ Rights, Contempt of Court, Penal Reform